Biochar-mediated detoxification of biofuel-derived toxins: A pathway-specific approach toward closed-loop biorefineries - Muhammad Rabah; Labeeb Ali; Mubarak Al-Kwradi; Mohammednoor Altarawneh (Journal of Environmental Chemical Engineering, 2026)

Fiber type-specific expression of LACTB leverages a function in oxidative metabolism - Kirsi-Marja Alanen; Rabah Soliymani; Jaakko Sarparanta; Satu Kuure; Kirsi Sainio; Zydrune Polianskyte; Muhammad Yasir Asghar; Ehsan Zangene; Annunziata Cascone; Maciej Lalowski; Peter Hackman; Johan Lundin; et al. (Histochemistry and Cell Biology, 2026)
Skeletal muscle is composed of type I and type II fibers, each characterized by specific metabolic machinery. LACTB is a conserved mitochondrial protein implicated in lipid utilization and tumorigenesis, but its precise function in the cellular metabolism remains unclear. To gain novel insight into the functional role of LACTB, we investigated skeletal muscle to determine whether LACTB is segregated by fiber type. The expression of LACTB was determined by immunohistochemistry (IHC) and immunoblotting in skeletal muscle from healthy human subjects and the laboratory rat. The specificity of the antibody was assessed using recombinant human LACTB protein and endogenous LACTB in isolated mitochondria. IHC results were validated in a cellular model of myoblast differentiation using the C2C12 and L6 cell lines. The results demonstrated that LACTB is highly enriched in adult type I muscle fibers. During development, LACTB expression commences in type I primary myotubes at the time of their formation around week 20 of gestational age. LACTB expression in myoblasts is low but increases rapidly upon the induction of myotube differentiation. We conclude that LACTB plays a distinct role in mitochondria of type I fibers, most likely acting in oxidative metabolism related to energy use from lipids. This defines LACTB as a mitochondrial marker for type I fibers.

Thermochemical conversion of bioplastics: Evolved gas analysis and kinetics factors for polylactic acid (PLA) - waste biomass mixture - Muhammad Rabah; Labeeb Ali; Mohamed Shafi Kuttiyathil; Mohammednoor Altarawneh (Biomass and Bioenergy, 2025)

Cowpea induced physicochemical and biological rhizosphere changes in hydrocarbon contaminated soil - A. A. Farouq; H. Y. Ismail; A. B. Rabah; A. B. Muhammad; U. B. Ibrahim; A. Y. Fardami (Plant and Soil, 2022)